A Framework for Financial Decisions in Multinational Corporations–Summary of Recent Research - Naumann-Etienne, Ruediger (Journal of Financial and Quantitative Analysis, 1974)
The purpose behind this review of recent research on financial decisions in the multinational corporation (MNC) has been, first, to further the discussion as to the appropriate normative framework applicable to financial decisions in the MNC, and second, to suggest directions for further research by pointing to open questions.The analysis focuses on the major financial decision areas of the firm as well as on important new factors introduced by the international environment. Specific issues disussed are: capital-market segmentation, financing decision, financial structure and cost of capital, investment decision and exchange risk.The principal conclusion presented as a basis for discussion is that the financial decision framework developed for the one-country firm can essentially be extended to the case of the MNC. This should hold true even if partial restrictions to capital flows exist. The only limiting requirement is that all subsidiaries be wholly owned, i.e., equity securities be issued by the parent firm only. A specific case in which the analogy to, the one-country firm breaks down arises when joint ventures are introduced.A number of areas for further research are identified. Most prominent, perhaps, are (1) an operational concept of economic exchange risk exposure, i.e., measuring the impact of exchange rate changes on the value of foreign operations; (2) criteria for evaluating foreign investment projects consistent with the firm's cost of capital; and (3) empirical evidence on the extent to which MNCs are affected by capital-market segmentation.